EFFECT OF UNBALANCED TOPOGRAPHY AND OVERLOADING ON COULOMB WEDGE KINEMATICS: INSIGHTS FROM SANDBOX MODELING - Del Castello M.; Pini G.A.; McClay K.R. (My University, 2004)
This study addresses the effect of variable unbalanced topography and overload on the kinematics of a fold and thrust belt developed within a collisional belt that underwent a subduction polarity reversal event. This was done by physical modeling of doubly vergent Coulomb wedges, using sand as an analogue material. During the experimental procedure a preexisting topography was generated by a first phase of subduction in one direction. A second phase of subduction was then initiated in the opposite direction (simulating a subduction flip). An anomalous, strong frontal growth for the wedge during the second phase was experimentally shown to be dependent upon surface slope breaks and the critical asymmetrical architecture achieved by the wedge at mature stages of deformation. The latter is suggested to be the rule for doubly vergent orogens at steady state, even after a subduction flip. During the experiments, surface processes, like syntectonic erosion and sedimentation, markedly altered mass transfer within the wedge. In particular, lowering the surface slope by syntectonic erosion favored cycling between accretion and underthrusting modes. By contrast, a sudden syntectonic sediment load in the prowedge region promoted prolonged phases of underthrusting, retarding accretion of new imbricates at the prowedge toe. However, at later stages of deformation the prowedge was forced to regain its characteristic minimum critical taper as predicted by theory and did so by the sudden nucleation of long, flat thrust units, rapidly rebalancing the asymmetry between prowedge and retrowedge regions. The experiments suggest that given a fixed critical taper related to time-invariant frictional properties along the wedge bounding surfaces, deformation does vary within the wedge according to time-varying location of normal stress surpluses and unbalanced topography acting on potential failure surfaces. These, in turn, alter the equilibrium between prowedge and retrowedge basal detachments that is here considered to be a major factor controlling the self-regulating dynamics of collisional orogens.
Keywords: sandbox modeling; wedge kinematics; unbalanced topography